Preparation method of grease-derived aperture-adjustable amorphous porous carbon

Through the method of adjusting the pores derived from oil and grease, no porous carbon preparation methods, using the mixed and flash heating techniques of fixed agents and oils to solve the problem of highly controlled and high energy consumption than the surface area of ​​the fixed porous carbon material, and achieve efficient and low energy. Preparation of materials consumed.

CN119349552APending Publication Date: 2025-01-24CHENGDU WANQIAN KEYAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411583418.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-05
Filing Date
2024-11-07
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The specific surface area of ​​existing amorphous porous carbon materials is difficult to control, and the energy consumption of conventional pyrolysis methods is high.

Method used

Pores derived from grease can be adjusted to prepare without fixed porous carbon. The steps such as uniform mixing, flash heating, and pickling of oil and fat are formed.

Benefits of technology

It achieves effective control of the specific surface area of ​​amorphous porous carbon materials, reduces energy consumption, and stabilizes the structure of carbon materials through the use of styling agents, which has commercial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349552A_ABST
    Figure CN119349552A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of grease-derived aperture-adjustable amorphous porous carbon, and relates to the field of amorphous porous carbon preparation, the method comprises the following steps: S1, uniformly mixing a setting agent and grease according to a ratio, and heating and stirring to form a grease block with specific micelles; s2, drying the grease blocks with the specific micelles to remove redundant water in the grease blocks, and shaping the micelles to form hole sites to prepare dried grease blocks; s3, carrying out rapid amorphous carbonization on the dried grease block by using a flash heating mode; s4, performing acid pickling to obtain a grease-derived primary mesoporous amorphous carbon-based material with specific uniform pore channels; and S5, washing the grease-derived primary mesoporous amorphous carbon-based material with water, then carrying out secondary flash heating, and shrinking the pore channels to prepare the pore-diameter-adjustable amorphous porous carbon. The problem that the specific surface area is also difficult to control in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of amorphous porous carbon preparation, and in particular to a method for preparing oil-derived amorphous porous carbon with adjustable pore size. Background Art

[0002] Amorphous porous carbon is a carbon material with a highly disordered structure and a large number of pores. It has a high specific surface area, rich pore structure and good chemical stability, so it has a wide range of application potential in adsorption, catalysis, electrochemical energy storage and other fields. The preparation methods of amorphous carbon include: carbide thermal decomposition method, carbonizing agent reduction method, vapor deposition method, etc. The preparation method that currently attracts more attention is mainly pyrolysis, that is, thermally decomposing the carbide-containing material under high temperature conditions to convert it into amorphous carbon.

[0003] However, conventional pyrolysis requires high-temperature treatment, consumes too much energy, and the specific surface area of ​​the carbon material is difficult to control. The vapor deposition method mainly deposits amorphous carbon materials on the substrate by pyrolyzing or chemically reacting carbon-containing gases at high temperatures. The carbon materials obtained by the vapor deposition method are relatively uniform, but the specific surface area is also difficult to control. Summary of the invention

[0004] The present invention provides a method for preparing amorphous porous carbon with adjustable pore size derived from oil and fat, which solves the problem that the specific surface area is also difficult to control in the prior art. The setting agent used in the present invention can stabilize the structure of the carbon material, and can also artificially adjust the pore size to form an amorphous porous carbon material. In addition, flash Joule heat can reduce a lot of energy consumption, achieve the purpose of efficient pyrolysis, reconstruction of morphology and pore formation in a short time, which not only reduces the impact on the environment, but also makes the oil and fat derived amorphous porous carbon process have commercial application prospects.

[0005] In order to solve this technical problem, the present invention provides the following technical solution:

[0006] The method for preparing oil-derived amorphous porous carbon with adjustable pore size comprises:

[0007] S1, uniformly mix the styling agent and the oil according to a certain proportion, heat and stir to form an oil block with specific micelles;

[0008] S2, drying the fat block with specific micelles to remove excess water therein, shaping the micelles to form pores, and obtaining a dry fat block;

[0009] S3, using flash heating to rapidly carbonize the dried grease block;

[0010] S4, obtaining a grease-derived primary mesoporous amorphous carbon-based material having specific uniform pores by pickling;

[0011] S5. The oil-derived primary mesoporous amorphous carbon-based material is washed with water and then flash-heated for a second time to shrink the pores to obtain an amorphous porous carbon with adjustable pore size.

[0012] The setting agent in step S1 is at least one of LiOH, KOH, NaOH, Mg(OH)2, Ca(OH)2, Ba(OH)2 or ammonia water;

[0013] The flash heating temperature in step S3 is 800-1100° C., the heating rate is 50-500° C. / s, and the total heating time is 10-90 seconds;

[0014] The flash heating temperature in step S5 is 1200-1500°C, the heating rate is 50-500°C / s, and the total heating time is 30-240s;

[0015] The pore size of microporous amorphous carbon-based materials is 0.5-2nm.

[0016] Step S1: The salts generated by the reaction of the alkaline substance with the oil form a stable micelle structure, which ensures that the oil block maintains its shape in the subsequent processing steps, is conducive to the formation of pores, and thus forms specific pore positions. The alkaline substance may catalyze the carbonization reaction under high temperature conditions, improve the carbonization efficiency, and make the amorphous carbon-based material form more quickly and effectively.

[0017] The rapid heating in step S3 can decompose the organic matter in the grease block to generate carbon in a short time, thereby improving the carbonization efficiency. High temperature can increase the molecular movement speed of volatile components, making it easier for them to escape from the mixture and form holes. Controlling the two affects the carbonization degree of the grease, thereby affecting the size of the pore size and the porosity.

[0018] In step S5, secondary heating is performed at a higher temperature, and the non-carbonized organic matter and other unstable components in the material will be further decomposed and removed, increasing the graphitization degree of the material itself, promoting further carbonization of the material, resulting in the shrinkage of the pores, and increasing its stability.

[0019] Preferably, the mass ratio of the setting agent to the oil in step S1 is 1-4.

[0020] The mixing ratio affects the stability of the micelle structure, which ensures that the formed micelles maintain their structure during subsequent processing and helps to form pores of appropriate size and distribution.

[0021] Preferably, in step S1, the heating temperature is 25-100° C., the stirring time is 0.5-2 hours, and the stirring speed is 100-400 r / min.

[0022] The stirring and mixing conditions ensure the mildness of the preparation process and maintain the stability of the micelle structure. The stirring conditions help to form a uniform and stable mixture, ensuring that the styling agent and the oil are fully mixed to form an oil mass with a stable micelle structure.

[0023] Preferably, in step S2, the drying temperature is 80° C. and the drying time is 5 hours.

[0024] Preferably, the pickling step in step S4 is to use at least one of hydrochloric acid, sulfuric acid, oxalic acid or nitric acid with a concentration of 1 mol / L for pickling, and the volume mass ratio of the acid dosage to the porous carbon material is 1-10 ml / g.

[0025] Reasonable acid dosage helps to effectively react with excess setting agent and other impurities, improve the purity of the material, and regulate the pore structure of the porous carbon material.

[0026] Preferably, the pore size of the oil-derived primary mesoporous amorphous carbon-based material is 2-50 nm.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] Compared with the prior art, the present invention proposes an efficient preparation method of oil-derived amorphous porous carbon with adjustable pore size. First, the ratio of the setting agent and the oil is adjusted to form a saponified oil block with specific micelles, and then the oil block is rapidly amorphously carbonized by flash heating. Finally, the oil-derived amorphous carbon-based material with specific uniform pores is obtained by acid washing and water washing.

[0029] The present invention uses a method of coating with a setting agent, and then uses a simple flash Joule heat reaction to effectively shorten the reaction time, and the added setting agent helps the structure of the oil to be stable during high-temperature pyrolysis, while the setting agent undergoes a dehydration reaction and reacts with carbon to produce a large number of bubbles, thereby achieving the purpose of adjustable pore formation. The porous carbon material obtained by the efficient preparation method of oil-derived amorphous porous carbon with adjustable pore size adopted by the present invention has a larger specific surface area, does not require complicated processes and higher energy consumption, and is very promising. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0031] Figure 1 It is a process flow chart of the present invention.

[0032] Figure 2 The nitrogen adsorption and desorption experimental data diagrams of different embodiments of the present invention;

[0033] Figure 3This is a cyclic charge and discharge test diagram of the sodium ion battery SIBs of Example 4;

[0034] Figure 4 This is the X-ray diffraction test diagram of the carbon material in Example 1;

[0035] Figure 5 This is the Raman test image of the carbon material in Example 1;

[0036] Figure 6 This is a scanning electron microscope image of the carbon material in Example 1. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0038] Example 1

[0039] like Figure 1 As shown, an efficient preparation method of oil-derived amorphous porous carbon with adjustable pore size is implemented by the following steps:

[0040] S1, KOH and oil were mixed in a mass ratio of 1:1, and stirred at a speed of 400 r / min for 1 hour at room temperature to form an oil block with specific micelles;

[0041] S2. Place the oil block in an oven at 80°C and heat for 5 hours to dry and remove excess water, so that the micelles are shaped to form pores.

[0042] S3, moving the dried grease block into a flash Joule heating device, heating it to 800°C, with a heating rate of 100°C / s, and a total heating time of 20 seconds, to rapidly carbonize the grease block;

[0043] S4, the carbonized material is naturally cooled to room temperature and then transferred into a beaker, 1 mol / L sulfuric acid solution with a volume (ml) twice the mass (g) of the material is added and stirred thoroughly, and then filtered to obtain a grease-derived primary mesoporous (pore size 2-50 nm) amorphous carbon-based material with specific uniform pores;

[0044] S5. Place the filtered material in a beaker again, add an aqueous solution twice the mass of the material and stir thoroughly, then filter and wash twice;

[0045] S6, the washed carbon material is moved into the flash Joule heating device again, the temperature is raised to 1500°C, the heating rate is 100°C / s, the total heating time is 50 seconds, and a microporous (pore size 0.5-2nm) amorphous carbon-based material is prepared by pore shrinkage;

[0046] Example 2

[0047] This embodiment provides a method for efficiently preparing oil-derived amorphous porous carbon with adjustable pore size, and the method is implemented by the following steps:

[0048] S1. KOH and oil were mixed in a mass ratio of 4:1, and stirred at 400 r / min for 1 hour at room temperature to form an oil block with specific micelles.

[0049] S2. Place the oil block in an oven at 80°C and heat for 5 hours to dry and remove excess water, so that the micelles are shaped to form pores.

[0050] S3. The dried grease block is moved into a flash Joule heating device, heated to 1100°C, with a heating rate of 500°C / s and a total heating time of 10 seconds, to rapidly carbonize the grease block.

[0051] S4. After the carbonized material is naturally cooled to room temperature, it is transferred into a beaker, and a 1 mol / L sulfuric acid solution with a volume (ml) 5 times the mass (g) of the material is added and stirred thoroughly, and then filtered to obtain an oil-derived primary mesoporous (pore size 2-50 nm) amorphous carbon-based material with specific uniform pores.

[0052] S5. Place the filtered material in a beaker again, add an aqueous solution twice the mass of the material and stir thoroughly, then filter and repeat washing twice.

[0053] S6. The washed carbon material is moved into the flash Joule heating device again, and the temperature is raised to 1200°C at a heating rate of 200°C / s. The total heating time is 30 seconds, and a microporous (pore size 0.5-2nm) amorphous carbon-based material is prepared by pore shrinkage.

[0054] Example 3

[0055] This embodiment provides a method for efficiently preparing oil-derived amorphous porous carbon with adjustable pore size, and the method is implemented by the following steps:

[0056] S1. KOH and oil were mixed in a mass ratio of 2:1, and stirred at 400 r / min for 1 hour at room temperature to form an oil block with specific micelles.

[0057] S2. Place the oil block in an oven at 80°C and heat for 5 hours to dry and remove excess water, so that the micelles are shaped to form pores.

[0058] S3. Move the dried grease block into a flash Joule heating device, heat it to 1000°C, with a heating rate of 50°C / s and a total heating time of 90 seconds, to perform rapid amorphous carbonization on the grease block.

[0059] S4. After the carbonized material is naturally cooled to room temperature, it is transferred into a beaker, and a 1 mol / L hydrochloric acid solution with a volume (ml) 10 times the mass (g) of the material is added and stirred thoroughly, and then filtered to obtain an oil-derived primary mesoporous (pore size 2-50 nm) amorphous carbon-based material with specific uniform pores.

[0060] S5. Place the filtered material in a beaker again, add an aqueous solution twice the mass of the material and stir thoroughly, then filter and repeat washing twice.

[0061] S6. The washed carbon material is moved into the flash Joule heating device again, heated to 1300°C, with a heating rate of 150°C / s and a total heating time of 240 seconds, and a microporous (pore size 0.5-2nm) amorphous carbon-based material is prepared by pore shrinkage.

[0062] like Figure 2 As shown, the materials obtained in Examples 1-3 were subjected to nitrogen adsorption and desorption experiments, and it was found that the prepared materials had both micropores and mesopores. The specific surface area of ​​Example 1 reached 2145.5 m 2 ·g -1 ,; The specific surface area of ​​the material prepared in Example 2 reached 1452m 2 ·g -1 ; Example 3 specific surface area reached 1799.8m 2 ·g -1 It can be seen that the ratio of setting agent to oil and fat and the flash Joule heat reaction time have a great influence on the specific surface area and performance of amorphous porous carbon; the effect of secondary Joule heat reaction at 1500℃ is better than that at 1200℃, and the ratio of setting agent to oil is more appropriate at 1:1.

[0063] Example 4

[0064] The oil-derived amorphous porous carbon material with adjustable wide pore size obtained in Example 1 is applied to the negative electrode of a sodium ion battery, and the specific steps are as follows:

[0065] Sodium sheet was used as electrode material, Whatman GF / D glass fiber was used as separator, and NaClO4 (1 mol / L) was used as electrolyte. The binder polyvinylidene fluoride, the conductive agent acetylene black and the electrode carbon material obtained in Example 1 were mixed uniformly in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone was added to make it evenly dispersed. Subsequently, the mixture was coated on the current collector copper foil, and roller pressing was performed after drying. Finally, the sample was punched into a disc with a diameter of 14 mm using a puncher for subsequent assembly of sodium ion batteries (CR2032 type).

[0066] Figure 3The charge and discharge diagram of the sodium ion battery in Example 4 after 1000 cycles (current density is 100 mAh / g) is shown in FIG. Figure 3 It can be seen that the carbon material used as the negative electrode of the battery exhibits excellent cycle stability. In the second cycle, the discharge capacity dropped rapidly from 410.5 mAh / g to 346.6 mAh / g. This phenomenon is mainly due to the formation of the solid electrolyte interface (SEI) layer and the permanent capture of Na in the pores. + ions. Starting from the second cycle, the reversible capacity decay slowed down significantly, further proving the stability of carbon materials in sodium storage. After 1000 cycles, the capacity remained stable at 316.8 mAh / g, and the Coulombic efficiency was maintained at about 100%, further verifying the reliable cycle performance of carbon materials as electrodes.

[0067] In order to further explore the energy storage mechanism of the material, the oil-derived amorphous porous carbon material with adjustable wide pore size obtained in Example 1 was characterized by X-ray diffraction, Raman spectroscopy and scanning electron microscopy.

[0068] Figure 4 The X-ray diffraction pattern of the oil-derived amorphous porous carbon with adjustable pore size in Example 1 is shown. An obvious broad peak is observed near 23.5°, corresponding to the (002) crystal plane of the amorphous carbon material. According to the Bragg equation and the position of the diffraction peak, the interlayer spacing of the material is calculated to be 0.378nm. The material has a large interlayer spacing, which is conducive to Na + intercalation and deintercalation, thereby improving the electrochemical performance.

[0069] Figure 5 The Raman spectrum of the material is shown. The D band and G band appear in the Raman spectrum, with the peak at 1590 cm -1 The G band is attributed to the ordered graphene structure, while the 1350 cm -1 The D band is related to disordered structure and lattice defects. The intensity of the D band is significantly higher than that of the G band, indicating that the material contains a large number of defects, which help to increase the Na + adsorption sites.

[0070] Figure 6 This is a scanning electron microscope image of the material. Figure 6 The carbon material particles have relatively smooth edges, with a particle size of about 2 μm, and are accompanied by some irregularly shaped flake aggregates. The rough surface is accompanied by the formation of a large number of micropores, which significantly increases the specific surface area and porosity of the material, thereby increasing the interaction with Na + contact sites, which helps to improve its energy storage performance.

[0071] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing amorphous porous carbon with adjustable pore size derived from oil, characterized in that: The steps include: S1, uniformly mix the styling agent and the oil according to a certain proportion, heat and stir to form an oil block with specific micelles; S2, drying the fat block with specific micelles to remove excess water therein, shaping the micelles to form pores, and obtaining a dry fat block; S3, using flash heating to rapidly carbonize the dried grease block; S4, obtaining a grease-derived primary mesoporous amorphous carbon-based material having specific uniform pores by pickling; S5, washing the oil-derived primary mesoporous amorphous carbon-based material with water and then flash-heating it for a second time, shrinking the pores to prepare an amorphous porous carbon with adjustable pore size; The setting agent in step S1 is at least one of LiOH, KOH, NaOH, Mg(OH)2, Ca(OH)2, Ba(OH)2 or ammonia water; The flash heating temperature in step S3 is 800-1100° C., the heating rate is 50-500° C. / s, and the total heating time is 10-90 seconds; The flash heating temperature in step S5 is 1200-1500°C, the heating rate is 50-500°C / s, and the total heating time is 30-240s; The pore size of the pore-adjustable amorphous porous carbon is 0.5-2 nm.

2. The method for preparing the oil-derived amorphous porous carbon with adjustable pore size according to claim 1, characterized in that: The mass ratio of the setting agent to the oil in step S1 is 1-4.

3. The method for preparing the oil-derived amorphous porous carbon with adjustable pore size according to claim 1, characterized in that: In step S1, the heating temperature is 25-100° C., the stirring time is 0.5-2 hours, and the stirring speed is 100-400 r / min.

4. The method for preparing oil-derived amorphous porous carbon with adjustable pore size according to claim 1, characterized in that: In step S2, the drying temperature is 80° C. and the drying time is 5 hours.

5. The method for preparing oil-derived amorphous porous carbon with adjustable pore size according to claim 1, characterized in that: The pickling step in step S4 is to use at least one of hydrochloric acid, sulfuric acid, oxalic acid or nitric acid with a concentration of 1 mol / L for pickling, and the volume mass ratio of the acid to the porous carbon material is 1-10 ml / g.

6. The method for preparing oil-derived amorphous porous carbon with adjustable pore size according to claim 1, characterized in that: The pore size of the oil-derived primary mesoporous amorphous carbon-based material is 2-50nm.